2019
DOI: 10.1088/1478-3975/ab1e76
|View full text |Cite
|
Sign up to set email alerts
|

Aggregation dynamics of active cells on non-adhesive substrate

Abstract: Cellular self-assembly and organization are fundamental steps for the development of biological tissues. In this paper, within the framework of a cellular automata model, we address how an ordered tissue pattern spontaneously emerges from a randomly migrating single cell population without the influence of any external cues. This model is based on the active motility of cells and their ability to reorganize due to cell-cell cohesivity as observed in experiments. Our model successfully emulates the formation of… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

6
2

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 65 publications
0
8
0
2
Order By: Relevance
“…Motivated by the experimental observations, we further investigated how the insulin fibrillation process is influenced by the presence of FA moieties in the FABC micelles based on a theoretical framework of diffusion-limited aggregation. [50][51][52][53] We first studied the aggregation process in the absence of FABC micelles. In our model, we consider "N" the number of insulin monomers randomly deposited on a (L × L) lattice system.…”
Section: Theoretical Modelmentioning
confidence: 99%
“…Motivated by the experimental observations, we further investigated how the insulin fibrillation process is influenced by the presence of FA moieties in the FABC micelles based on a theoretical framework of diffusion-limited aggregation. [50][51][52][53] We first studied the aggregation process in the absence of FABC micelles. In our model, we consider "N" the number of insulin monomers randomly deposited on a (L × L) lattice system.…”
Section: Theoretical Modelmentioning
confidence: 99%
“…Experiments performed by Steinberg and collaborators demonstrated that cell aggregation and selective spreading of cells in a mixed cell population could occur simply due to the differences in the interfacial adhesion strength even in the absence of any differential chemical cues [42] which could be explained by Differential adhesion hypothesis (DAH). DAH provides an insight into such aggregation of cohesive cells and inspired many discrete cell models to understand various morphological structures during the development [20-–23, 43, 44]. We construct our model based on DAH, where motile and cohesive cells spontaneously adhere with each other to maximize the cohesive binding strength and minimize the cell-ECM interfacial energy of the system.…”
Section: Theoretical Modelmentioning
confidence: 99%
“…Cohesive group formation is one of the most eyecatching displays in nature. It is observed among various species, such as, flock of birds [1, 2], school of fishes [3], swarm of prey [4,5], colony of bacteria [6], aggregation of cells [7], and pedestrian crowd [8]. The instances of collective behaviours have also been demonstrated in non-living systems including multi-agent robots [9], vibrated disks [10], artificial microswimmers [11] etc.…”
Section: Introductionmentioning
confidence: 99%